Enzymatic synthesis of lipids containing omega-3 fatty acids - Lyberg, Ann-Marie (Department of Biotechnology, Lund University, 2007)
Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are omega-3 fatty acids, which have health promoting effects. Since they are highly prone to oxidation, they should be protected, in particular DHA. Several lipids containing DHA were evaluated with respect to the ability of the lipids to protect DHA against peroxidation using an HPLC method developed as part of this research. Furthermore, the protection of free DHA in a liposome system containing antioxidants was investigated. The phospholipids offered protection against peroxidation when DHA was incorporated at one position of either phosphatidylcholine or phosphatidylethanolamine. Furthermore, alfa-tocopherol combined with ascorbic acid offered the best protection to free DHA in a liposome system containing phosphatidylcholine. Enzymatic methods were developed to incorporate either DHA or EPA at the sn-1 position of 2-acyl-lysophosphatidylcholine. Since the enzymes utilised discriminated against these fatty acids, in particular DHA, screening for the appropriate enzyme was performed. Among the investigated lipases, those from Candida antarctica and Rhizopus arrhizus showed the best performance in incorporating DHA and EPA, respectively. The incorporation of these fatty acids could be increased by performing the reaction at a water activity of 0.22, which allowed some hydrolysis to occur simultaneously with the esterification. Since DHA and EPA were discriminated against in both reactions, the content of these fatty acids in the synthesised phosphatidylcholine was increased with reaction time. The ability of the lipases to discriminate against DHA and EPA was utilised to enrich these fatty acids in fish oil and squid oil. Furthermore, the competitive factors for both EPA and DHA were evaluated in both marine oils and a mixture of methyl esters. Hydrolysis of all substrates and ethanolysis of squid oil were performed, converting mainly other fatty acids and leaving DHA and/or EPA in the substrate. The competitive factors achieved for DHA and EPA were ...